Hubungan Antara Self Esteem dengan Kecenderungan Perilaku Seksual Pranikah Pada Dewasa Muda - Dominico, Catherine Agnesia Putri; Kristianingsih, Sri Aryanti (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the relationship between self-esteem and the tendency of premarital sexual behavior among young adults. This study is based on the increasing prevalence of premarital sexual behavior in Indonesia, especially among young adults, and highlights the importance of understanding the psychological factors involved. This quantitative correlational study involved 402 active students aged 18–25 years at Satya Wacana Christian University who reported engaging in premarital sexual behavior. The instruments used included the Rosenberg Self-Esteem Scale (RSES) and the premarital sexual behavior scale based on Walker's theory. Spearman's Rho analysis showed a very weak and insignificant negative correlation (r = -0.009; p > 0.05), indicating no significant relationship between self-esteem and premarital sexual behavior. These findings suggest that self-esteem is not a major determinant of premarital sexual behavior in young adults. This study provides theoretical implications for the development of literature in developmental and social psychology, and practical implications for educational interventions aimed at young adults.